Plato's psychology - Robinson, T. M. (Phoenix. Supplementary volume, 2018)
Plato's Psychology originally published in 1970 and reprinted in 1972, is still the definitive modern discussion of the nature and development of Plato's concept of psyche. In a lengthy and detailed new introduction T.M. Robinson surveys the scope and value of a number of contributions to Plato's theory of psyche, individual and cosmic, that have appeared since 1970. He then offers his own 'second thoughts' on various aspects of the subject, revisiting inter alia such questions as the dating of the Timaeus, and the implication thereof, and the understanding and implications of the myth of the Politicus. Finally, he widens the whole discussion of Plato's cosmic psychology to include an analysis and appreciation of the remarkably close relationship between much of Plato's thinking about the universe and its origins and a good deal of twentieth-century theorizing, from Einstein to Hawking.